2005
DOI: 10.1677/joe.1.06022
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid status and nitric oxide in rat arterial vessels

Abstract: Thyroid disease has profound effects on cardiovascular function. Hypo-and hyperthyroidism, for example, are associated with reduced and increased maximal endothelium-dependent vasodilation respectively. We therefore hypothesized that the capacity for vascular nitric oxide (NO) formation is decreased in hypothyroidism and increased in hyperthyroidism. To test this hypothesis, rats were made hypothyroid (HYPO) with propylthiouracil or hyperthyroid (HYPER) with triiodothyronine over 3-4 months. Compared with euth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 32 publications
2
41
1
6
Order By: Relevance
“…Thus, we cannot definitively conclude that arteriolar remodeling and tissue hypothyroidism led to impaired coronary flow in this study. However, numerous previous reports have confirmed that coronary flow is impaired by diabetes, low TH conditions and/or arteriolar remodeling and is augmented by or preserved with thyroid hormone treatment (4,13,(25)(26)(27)(54)(55)(56). Third, we were unable to find reliable commercial antibodies needed to confirm protein expression changes for the reported TH transporters, cytosolic binding proteins.…”
Section: +mentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, we cannot definitively conclude that arteriolar remodeling and tissue hypothyroidism led to impaired coronary flow in this study. However, numerous previous reports have confirmed that coronary flow is impaired by diabetes, low TH conditions and/or arteriolar remodeling and is augmented by or preserved with thyroid hormone treatment (4,13,(25)(26)(27)(54)(55)(56). Third, we were unable to find reliable commercial antibodies needed to confirm protein expression changes for the reported TH transporters, cytosolic binding proteins.…”
Section: +mentioning
confidence: 77%
“…It is well established that diabetic hearts are at an increased risk for both macro-and microvascular pathology and although many factors likely contribute to diabetic vascular dysfunction (for example, hyperglycemia, reactive oxygen species), low cardiac tissue TH levels may contribute to or exacerbate microvascular dysfunction in diabetic hearts. Cardiac microvessel remodeling, endothelial dysfunction, increased arteriolar tone/vasoreactivity, decreased vascular growth factor expression, impaired myocardial blood flow and diminished blood flow reserve are common features of both DM and overt/subclinical hypothyroidism (4,13,(25)(26)(27)(54)(55)(56).…”
Section: +mentioning
confidence: 99%
“…During CPT, increased shear stress stimulates the coronary endothelial cell to release NO, which mediates relaxation of microcirculatory smooth cells and increases perfusion. Animal studies have indicated that thyroid dysfunction can alter capacities for the formation and response to NO (31). A recent study suggests that T 3 rapidly stimulates phosphatidylinositol 3-kinase/Akt signaling and increases nitric acid synthase activity 'nitric oxide synthase' in endothelial cells by a receptor-mediated non-genomic action, and thus induces vasodilatation (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, rarefaction of myocardial arterioles has been observed recently in endothelial NO synthase (eNOS) knockout mice, 41 and NO availability and eNOS are known to be reduced in hypothyroidism. 42,43 Consequently, reduced eNOS in hypothyroidism may play an important role in arteriolar rarefaction in this disorder. This possibility merits further investigation.…”
Section: Tang Et Almentioning
confidence: 99%
“…It is also worth noting that upregulation of eNOS is a strong candidate for thyroid hormone-induced coronary angiogenesis. 42,44 It should be appreciated that PTU affects many aspects of thyroid hormone metabolism, including iodination, coupling, and deiodination of T4. [45][46][47] There is also a possibility that PTU may have a direct toxic effect on coronary arterioles.…”
Section: Tang Et Almentioning
confidence: 99%